Pemberdayaan Masyarakat Melalui Pembuatan Pupuk Organik Bokashi Kelurahan Sangpiak Salu - Samrius Upa; Hans Lura; Arun Rerung Bontong (Jurnal Pengabdian Masyarakat Waradin, 2024)
This research aims to increase agricultural productivity and empower the community through the manufacture of bokashi organic fertilizer in Sangpiak Salu Village. This activity involves the utilization of organic waste, especially livestock manure, which is fermented using effective microorganisms (EM4) to produce quality fertilizers. The results of the study show that the use of bokashi fertilizer significantly increases plant growth, improves soil structure, and provides economic added value for farmers. In addition, this program has also succeeded in increasing public awareness of the importance of sustainable agriculture.